PERAN QARYAH THAYYIBAH AISYIYAH POSYANDU BALITA MENINGKATKAN PARTISIPASI KUNJUNGAN IBU BALITA : STUDI KUALITATIF - Noor Azizah; Sri Karyati; Dwi Astuti; Salis Nur Hidayah (Universitas Muhammadiyah Kudus, 2024)
Aisyiyah fights for the rights of men and women where equality of rights is based on ability, regardless of appearance or gender. One of the aisyiyah qaryah thayyibah programs in the health sector is the establishment of a posyandu for toddlers. The purpose of this study is to find out the role of aisyiyah in the formation of qaryah thayyibah in the health sector through the activities of posyandu toddlers. This research is a qualitative phenomenology research. Subject selection using purposive sampling. Data collection using in-depth interviews and observations. An in-depth interview was conducted with the person in charge of the posyandu program, posyandu cadres, and posyandu visitors. Observations were made on the activities of the Posyandu for toddlers. Analyze data using Content Analysis. The results in this study are that QTA posyandu for toddlers was established by PDA Kudus through the Health Council and established in PRA Cendono, the implementation of posyandu once a month on the 13th, the obstacle to the number of cadres has not been maximized. Conclusion of Qaryah Thayyibah Aisyiyah posyandu toddler at PRA Cendono as a form of Aisyiyah's work on maternal and child health. The participation of cadres, infrastructure facilities and funds for the provision of additional food for toddlers is a supporting factor in the implementation of posyandu. The implementation of posyandu in the afternoon increases participation for mothers who have babies because they have free time after work. QTA Posyandu toddlers need to be trained to improve the abilities and skills of cadres and develop to the elderly posyandu adolescents so that Aisyiyah in the health sector pays attention to health from infants to the elderly.